Discovery Learning Research in Mathematics Learning: A Bibliometric Review - Ilham Muhammad; Rani Darmayanti; Viky Risnanda Arif; Adebayo Ola Afolaranmi (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
Discovery Learning is a learning model that changes learning from teacher-centred learning to student-centred learning so that students learn actively by discovering themselves, investigating themselves and cultivating a scientific attitude. The purpose of this research is to discover the research focus related to Discovery Learning in learning mathematics and its novelty. The method used is bibliometric analysis. The data taken comes from the Scopus database. The study results show increased publications related to Discovery Learning in mathematics learning from 2017 to 2023. The highest citation trend occurred in the 2017 publication, which has been cited 41 times. The country that has had a major impact on Discovery Learning research in mathematics learning is Indonesia. The research focus is divided into three parts, namely, 1) Discovery Learning, Mathematics Learning and student; 2) problem-solving and Indonesia; 3) junior high school and Geometry. New themes in this field are e-learning, teaching and learning, mathematical software, pre-service teachers, and technology.